2014
DOI: 10.1155/2014/212098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wonli Acupuncture Procedure in Patients with LSS: A Clinical, Retrospective Study

Abstract: Background. Lumbar spinal stenosis (LSS) is a disease with increasing prevalence due to prolongation of average life span. Despite various treatment methods, many limitations remain unsolved. Objective. We are reporting cases of patients who have been treated with Wonli Acupuncture, a method of treating LSS by directly approaching the intervertebral foramen and interlaminar space with acupuncture needles different from those used in original acupuncture. Methods. A total of 82 patients with LSS were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Thus, treating the affected region of LDH with acupotomy is considered to reduce the physical pressure on the nerve roots and activate the microcirculation, consequently improving low back pain and/or leg pain. 36 Inoue et al implemented a clinical trial to evaluate the effectiveness of electroacupuncture treatment on low back pain and lower limb symptoms. 37 They carried out electroacupuncture stimulation of the nerve root under an X-ray fluoroscope; this resulted in immediate relief, which was sustained until follow-up at the 3 months time point in two of the three patients diagnosed with LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treating the affected region of LDH with acupotomy is considered to reduce the physical pressure on the nerve roots and activate the microcirculation, consequently improving low back pain and/or leg pain. 36 Inoue et al implemented a clinical trial to evaluate the effectiveness of electroacupuncture treatment on low back pain and lower limb symptoms. 37 They carried out electroacupuncture stimulation of the nerve root under an X-ray fluoroscope; this resulted in immediate relief, which was sustained until follow-up at the 3 months time point in two of the three patients diagnosed with LDH.…”
Section: Discussionmentioning
confidence: 99%
“…The use of KA and BTA on lumbar spinal stenosis was reported before [18]. But this is the first research of KA and BTA on patients with cervical radiculopathy.…”
Section: Minimally Invasive Widening Of the Facet Joints In Cervical mentioning
confidence: 95%
“…It has been used for treating chronic pain and eliminating obstinate lesions by incising the synechia and removing the attached tissue with a flat-head bladed needle. 5 , 6 Although it has more recently been investigated in Korea, the use of acupotomy has increased among Korean Medicine Doctors. Furthermore, an advanced acupotomy procedure with newly developed needles has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an advanced acupotomy procedure with newly developed needles has been proposed. 6 According to a review of the trends in acupotomy from January 1999 to May 2014, 7 many studies have focused on musculoskeletal diseases arising in the neck and low back. In addition, four case studies regarding lumbar disc herniation reported improvements in pain and disability after acupotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation